Endemic erythromycin resistant Corynebacterium diphtheriae in Vietnam in the 1990s. Issue 10 (19th October 2022) - Nguyen Thi Nguyen, To; Parry, Christopher M.; Campbell, James I.; Vinh, Phat Voong; Kneen, Rachel; Baker, Stephen
Abstract : Diphtheria is a potentially fatal respiratory disease caused by toxigenic forms of the Gram-positive bacterium Corynebacterium diphtheriae . Despite the availability of treatments (antitoxin and antimicrobials) and effective vaccines, the disease still occurs sporadically in low-income countries and in higher income where use of diphtheria vaccine is inconsistent. Diphtheria was highly endemic in Vietnam in the 1990s; here, we aimed to provide some historical context to the circulation of erythromycin resistant organisms in Vietnam during this period. After recovering 54 C . diphtheriae isolated from clinical cases of diphtheria in Ho Chi Minh City between 1992 and 1998 we conducted whole genome sequencing and analysis. Our data outlined substantial genetic diversity among the isolates, illustrated by seven distinct Sequence Types (STs), but punctuated by the sustained circulation of ST67 and ST209. With the exception of one isolate, all sequences contained the tox gene, which was classically located on a corynebacteriophage. All erythromycin resistant isolates, accounting for 13 % of organisms in this study, harboured a novel 18 kb erm(X )-carrying plasmid, which exhibited limited sequence homology to previously described resistance plasmids in C. diphtheriae . Our study provides historic context for the circulation of antimicrobial resistant C. diphtheriae in Vietnam; these data provide a framework for the current trajectory in global antimicrobial resistance trends.